Review of measurement techniques for void fraction of two-phase flow through annulus. (1st December 2020) - Ghendour, Nabil; Meribout, Mahmoud; Azzi, Abdelwahid
Abstract: This paper presents a state of the art measurement and imaging systems used to determine the Gas Void Fraction (GVF) of two-phase flow through annuli. Several research works were conducted for GVF measurement of two and three-phase fluids flowing through full circular pipelines but only few of them targeted the annuli. The highly restricted access and the low volume within which the multiphase fluid flows through in annuli make the instrumentation design challenging. This is especially true if non-intrusive sensors are required to not disturb the flow, which is the case, for instance, if an accurate CFD modeling of annulus flow is sought out of these measurements. Motivated by the numerous industrial applications of annuli, several researchers have suggested various corresponding non-invasive GVF measurement devices to better understand the behavior of the annulus flow and also to determine the production rate. Many of these techniques are based on electrical conductivity measurements using one or several pairs of electrodes. Various configurations of the electrodes were suggested and this paper highlights that none of them can cope with all kinds of flow patterns. Imaging techniques using wire mesh and electrical resistance tomography were also suggested and the initial corresponding results were very encouraging. This paper provides a critical review of each of these techniques and highlights the advantages, disadvantages, and limitations of each one. Hence, it can be a valuable research reference for either new scientists in the area of instrumentation to design a sensor targeting annulus flow or to experienced engineers and researchers to keep in touch with the most recent research advances in the area.